2012
DOI: 10.1002/ajhb.22321
|View full text |Cite
|
Sign up to set email alerts
|

Is skinfold thickness as good as DXA when measuring adiposity contributions to insulin resistance in adolescents?

Abstract: Triceps and subscapular skinfold thicknesses estimate HOMA-IR and identify those at highest risk for insulin resistance as well as total body fat from DXA. Skinfold thickness provides an inexpensive and widely applicable measure of fatness that is appropriate for studies of insulin resistance and perhaps other metabolic variables in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…19 Although BMI is the most commonly used proxy for determining adiposity in youths, indices such as sum of skin folds or dual-energy X-ray absorptiometry are considered gold standards. 20 The proportions of overweight (16.3%) and obese (5.2%) youths in the current study are slightly lower than expected on the basis of national Canadian data, 7 although evidence has suggested that adolescents may underestimate their weight in self-reported data, particularly those who are overweight. 21 This may result in a low BMI calculation and misclassification (e.g., overweight classified as normal weight).…”
Section: Discussioncontrasting
confidence: 64%
“…19 Although BMI is the most commonly used proxy for determining adiposity in youths, indices such as sum of skin folds or dual-energy X-ray absorptiometry are considered gold standards. 20 The proportions of overweight (16.3%) and obese (5.2%) youths in the current study are slightly lower than expected on the basis of national Canadian data, 7 although evidence has suggested that adolescents may underestimate their weight in self-reported data, particularly those who are overweight. 21 This may result in a low BMI calculation and misclassification (e.g., overweight classified as normal weight).…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, birth weight alone cannot distinguish between appropriate body composition or excessive fat stores. Using a combination of skinfold thickness [36,47], ponderal index [32], leanness and birth shape [33], we have shown for the first time that, in addition to birth weight, markers of adiposity are associated with increased aortic IMT; and conversely, that leanness is associated with decreased aortic IMT. Importantly, even after adjustment for birth weight and aortic size, the association between birth skinfold thickness and aortic IMT persisted.…”
Section: Discussionmentioning
confidence: 93%
“…percentage body fat) and could perhaps be indicative of the phenomenon of increasing anthropometric measurements. A study conducted in 2012 by Addo et al among adolescents in the United States showed that skinfolds (tricep and subscapular) were able to identify individuals at risk of developing IR [ 89 ]. The sum of skinfolds could perhaps be used as a marker to identify those at risk of developing IR, which may be prudent in populations that do not exhibit typical metabolic syndrome-like characteristics.…”
Section: Discussionmentioning
confidence: 99%